Immunogenicity and safety of two-dose SARS-CoV-2 vaccination via different platforms in kidney transplantation recipients - Chen, Chien-Chia; Huang, Yi-Jen; Lai, Mei-Jun; Lin, Min-Huey; Lin, Wei-Chou; Lin, Hui-Ying; Lin, Yu-Chun; Huang, Yu-Tsung; Lee, Ya-Fen; Tsai, Meng-Kun; Lee, Chih-Yuan (Frontiers in Immunology, 2022)
After kidney transplantation, patients exhibit a poor response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination. However, the efficacy and adverse effects of vaccines based on different platforms in these patients remain unclear. We prospectively analyzed both anti-spike protein antibody and cellular responses 1 month after the first and second doses of SARS-CoV-2 vaccines in 171 kidney transplant patients. Four vaccines, including one viral vector (ChAdOx1 nCov-19, n = 30), two mRNA (mRNA1273, n = 81 and BNT162b2, n = 38), and one protein subunit (MVC-COV1901, n = 22) vaccines were administered. Among the four vaccines, mRNA1273 elicited the strongest humoral response and induced the highest interferon-γ levels in patients with a positive cellular response against the spike protein. Antiproliferative agents were negatively associated with both the antibody and cellular responses. A transient elevation in creatinine levels was noted in approximately half of the patients after the first dose of mRNA1273 or ChadOx1, and only one of them presented with borderline cellular rejection without definite causality to vaccination. In conclusion, mRNA1273 had better immunogenicity than the other vaccines. Further, renal function needs to be carefully monitored after vaccination, and vaccination strategies should be tailored according to the transplant status and vaccine characteristics.